The Impulse Buying of Gen Z When Using E-Wallet In Indonesia - Lim Sanny; Gilang Rafi Chandra; Kitsy Chelles; Laurent Angelica Santoso (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
This research aims to analyze the impulse buying of Gen Z when using e-wallets in Indonesia. This type of research is quantitative research using the Partial Least Squares Structural Equation Modeling (SEM) framework. The sampling technique involved convenience sampling with a total of 393 Gen Z e-wallet users in Indonesia who had been surveyed online. Theoretical implications in this study are implementing the S-O-R framework on e-wallet enriches. This research provides a new perspective using Generation Z as a research subject. The results found in this study revealed that the model could explain 60.2% of variance satisfaction and 5.9% of impulse buying. In addition, the factors that encourage satisfaction include perceived interactivity, perceived risk, and subjective norms that significantly affect satisfaction with a small effect. Perceived usefulness is the most significant factor with a substantial impact that positively influences satisfaction. This satisfaction is proven to control impulse buying positively, but it can only be explained in a small part. The research's practical implication is that these results can provide input for e-wallet development companies to satisfy Gen Z using e-wallets in impulse buying.